Evaluation of fish consumption in public markets in the city of Recife/PE (Research, Society and Development, 2022)
The Food and Agriculture Organization of the United Nations (FAO) recommends that fish consumption be 20kg per capita/year, however in Brazil it is still at 12kg per capita/year. During the Covid-19 pandemic, this reality suffered a strong impact due to price increases, shortages in supply and consumer evasion due to the lockdown. The objective of the study was to verify the practices of fish consumption, distinguish the consumer public during the pandemic period of Covid-19. The survey found that 64% of consumers were women and 36% men. The age group was above 40 years (42%); between 30 and 40 years (29%); 21 to 29 years (20%) and up to 20 years (9%). Acquisition preferences were gutted fish (36%); fish in steak (34%); fish fillet (26%) and whole fish (4%). In the opinion of consumers, commercialization spaces and flow areas present visible dirtiness, transit of companion animals, poor cleaning procedures, described scenarios that can compromise commercialized fish, due to cross-contamination.